NGHIÊN CỨU CHẾ TẠO GỐM XỐP HYDROXYAPATIT TỪ ĐÁ VÔI BẰNG PHƯƠNG PHÁP PHẢN ỨNG THỦY NHIỆT - Hương, Đào Quốc; Sao, Phạm Thị (Vietnam Journal of Science and Technology, 2012)
SYNTHESIS OF POROUS HYDROXYAPATITE CERAMICS FROM LIMESTONE VIA HYDROTHERMAL PROCESS Porous hydroxyapatite (HA) ceramics was prepared by hydrothermal method from limestone in two ways: synthesized directly from limestone (calcite CaCO3) and synthesized from CaO, which was product of limestone thermal decomposition. Conditions of hydrothermal reaction are 200oC,15 atm in 24 hours. The samples were characterized by XRD, SEM, DTA/TGA and FTIR. The results confirmed that ceramics of single phase HA was formed by the indirect synthesized from limestone obtained CaO. Water played an important role as the reactant and as solvent in the formation of HA by hydrothermal process. After the calcination at 1000oC in 1 hour, porous ceramics was structured by three-dimentional interconnected pores of 100 to 300 nm. XRD and FTIR characterizations of obtained HA are similar to HA references materials of NIST.